2020
DOI: 10.1021/acs.energyfuels.9b03695
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Oxidation Behavior of Automotive Liquefied Petroleum Gas Fuels: Experimental and Kinetic Analyses

Abstract: Liquefied petroleum gas (LPG) is a low-carbon fuel with an existing fuel supply infrastructure. As compared to petroleum-based gasoline, it features a higher octane rating. As compared to port fuel injection (PFI) systems, the direct injection (DI) of LPG engines reveals significant advantages in modern spark-ignition, such as higher efficiency. LPG primarily consists of C 3 and C 4 hydrocarbons, but the composition can drastically vary according to the current European LPG fuel standard EN 589. Several studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The primary goal of this study is to develop a consistent mechanism that can represent the auto-ignition behavior of propane, propene, and their mixtures over a wide range of temperature, pressure, mixture composition, and dilution. The mechanism development is a continually evolving process, and the experimental work established in this work and from previous studies [9,10] has contributed to the development of NUIGMech1.0. The study on automotive LPG fuels [9] and the previous study on propane [10] showed that mechanisms available in the literature do not capture the reactivity for the neat components and their mixtures in a consistent way.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…The primary goal of this study is to develop a consistent mechanism that can represent the auto-ignition behavior of propane, propene, and their mixtures over a wide range of temperature, pressure, mixture composition, and dilution. The mechanism development is a continually evolving process, and the experimental work established in this work and from previous studies [9,10] has contributed to the development of NUIGMech1.0. The study on automotive LPG fuels [9] and the previous study on propane [10] showed that mechanisms available in the literature do not capture the reactivity for the neat components and their mixtures in a consistent way.…”
Section: Introductionmentioning
confidence: 85%
“…The mechanism development is a continually evolving process, and the experimental work established in this work and from previous studies [9,10] has contributed to the development of NUIGMech1.0. The study on automotive LPG fuels [9] and the previous study on propane [10] showed that mechanisms available in the literature do not capture the reactivity for the neat components and their mixtures in a consistent way. In this study, the experimental work on propene is extended to higher pressures (80 bar) for stoichiometric mixtures in a rapid compression machine (RCM).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations